Lenvatinib Plus Camrelizumab vs. Lenvatinib Monotherapy as First-Line Treatment for Unresectable Hepatocellular Carcinoma: A Multicenter Retrospective Cohort Study - Li, Qi; Cao, Mengran; Yuan, Guosheng; Cheng, Xiao; Zang, Mengya; Chen, Ming; Hu, Xiaoyun; Huang, Jing; Li, Rong; Guo, Yabing; Ruan, Jian; Chen, Jinzhang (Frontiers in Oncology, 2022)
Background Combining an antiangiogenic agent with an anti-PD-1 agent is a promising strategy for unresectable hepatocellular carcinoma (HCC). Aims To explore the effectiveness and tolerability of lenvatinib plus camrelizumab vs. lenvatinib monotherapy as a first-line treatment for unresectable HCC. Methods This multicenter, retrospective cohort study included patients with unresectable HCC treated with oral lenvatinib 8 mg daily and intravenous camrelizumab 200 mg every 3 weeks (L+C group) or lenvatinib 12 mg or 8 mg daily (L group) in four Chinese centers between September 2018 and February 2020. Tumor response was evaluated according to RECIST 1.1 and mRECIST. The outcomes included objective response rate (ORR), overall survival (OS), 1-year OS rate, progression-free survival (PFS), and safety. Results By March 31, 2021, 92 patients were finally included, with 48 and 44 in the L+C and L groups, respectively. ORR was significantly higher in the L+C group than in the L group (RECIST 1.1: 37.5% vs. 13.6%, P=0.009; mRECIST: 41.7% vs. 20.5%, P=0.029). Median OS and 95% confidence interval (CI) was 13.9 (13.3-18.3) months in the L group and not reached in the L+C group (P=0.015). The 1-year survival rate was 79.2% and 56.8% in the L+C and L groups, respectively. Median PFS was 10.3 (6.6-14.0) months and 7.5 (5.7-9.3) months in the L+C and L groups, respectively (P=0.0098). Combined therapy vs. monotherapy was independently associated with a prolonged OS (hazard ratio=0.380, 95% CI=: 0.196-0.739, P=0.004) and a prolonged PFS (hazard ratio=0.454, 95%CI=0.282-0.731, P=0.001). The safety profile was comparable between the two groups. The most common adverse event in the L+C and L groups was loss of appetite (41.7% vs. 40.9%, P=0.941). Three patients in the L+C group and two in the L group terminated treatment owing to adverse events. Conclusion First-line lenvatinib plus camrelizumab showed better effectiveness than lenvatinib alone in patients with unresectable HCC.